Big data analytics for intelligent healthcare management - Dey, Nilanjan, 1984-; Das, Himansu; Naik, Bighnaraj; Behera, Himansu Sekhar (Advances in ubiquitous sensing applications for healthcare ;, 2019)
Big Data Analytics for Intelligent Healthcare Management covers both the theory and application of hardware platforms and architectures, the development of software methods, techniques and tools, applications and governance, and adoption strategies for the use of big data in healthcare and clinical research. The book provides the latest research findings on the use of big data analytics with statistical and machine learning techniques that analyze huge amounts of real-time healthcare data.